Computational fluid dynamics modelling and simulation of an inclined horizontal axis hydrokinetic turbine (2018)
In this contribution, unsteady three-dimensional numerical simulations of the water flow through a horizontal axis hydrokinetic turbine (HAHT) of the Garman type are performed. This study was conducted in order to estimate the influence of turbine inclination with respect to the incoming flow on turbine performance and forces acting on the rotor, which is studied using a time-accurate Reynolds-averaged Navier-Stokes (RANS) commercial solver. Changes of the flow in time are described by a physical transient model based on two domains, one rotating and the other stationary, combined with a sliding mesh technique. Flow turbulence is described by the well-established Shear Stress Transport (SST) model using its standard and transitional versions. Three inclined operation conditions have been analyzed for the turbine regarding the main stream: 0◦ (SP configuration, shaft parallel to incoming velocity), 15◦ (SI15 configuration), and 30◦ (SI30 configuration). It was found that the hydrodynamic efficiency of the turbine decreases with increasing inclination angles. Besides, it was obtained that in the inclined configurations, the thrust and drag forces acting on rotor were lower than in the SP configuration, although in the former cases, blades experience alternating loads that may induce failure due to fatigue in the long term. Moreover, if the boundary layer transitional effects are included in the computations, a slight increase in the power coefficient is computed for all inclination configurations